Brain immune system signal molecules in protection from aerobic and anaerobic infections - Galoyan, Armen A. (Advances in Neurobiology, 2012)
Dr. Galoyan is a pioneer of the specialized field of neuroimmunology. During his 45-year-long career, he has discovered a neuroendocrine immune system of the brain and identified a new type of brain cytokines: proline-rich polypeptides. The most important of these, PRP-1 (galarmin) has been shown to possess antibacterial properties and protect from certain neurotoxins. Proline-rich polypeptides-in particular (PRP-1) galarmin and its structural analogues-are, when isolated from the neurosecretory granules of neurohypophysis of humans and animals, a new type of hypothalamic peptides. They work against aerobic, anaerobic, gram-positive, and gram-negative microorganisms in vivo, and do not have etiotropic properties. They are unique and capable substitutes to antibiotics, and, moreover, may be effective against strains, such as MRSA, that develop resistance to antibiotics. Galarmin, a component of the brain neuroendocrine system produced by the neurosecretory cells of hypothalamus, possesses  immunomodulative, neuroprotective, antioxidant, antitumorigenic and hematopoietic properties. Moreover, galarmin and its structural analogues are powerful anti-inflammatory  compounds.  In addition to presenting a full overview of the neuroimmune system, it emphasizes the antibacterial, neuroprotective, and neuroregenerative properties of proline-rich polypeptides.  It investigates the mechanism of galarmin's action during different infectious processes, where it targets such dangerous pathogens as  Bacillus anthracis, Clostridium perfringens, Mycobacterium tuberculosis, and Methycillin resistant Staphylococcus aureus.   This research is important from both a theoretical and clinical point of view, creating new prospects for the modern pharmaceutical industry and neuroendocrine, neuroimmunological sciences.